Paisaje y nacionalismo en el primer franquismo. - Box, Zira (Hispanic Research Journal, 2016)
Assuming the theoretical idea widely developed by Human Geography that landscapes are cultural constructions with the capacity to become symbolic elements within nationalist discourses, this article explores the context of early Francoism. The aim of these pages is to analyze landscape sensibility as well as the landscape idea developed by the francoist nationalist discourse by trying to draw out three inherent elements in it: first of all, following Oliver Zimmer’s work, the nationalization of nature, this is to say, the consideration that nature expresses the community’s myths, events or memories; secondly, the naturalisation of the nation, that projects upon landscapes the capacity to determine the national character; finally, the power that landscapes — especially, those considered asnational landscapes— have to impress human beings.